Developments on chemometric approaches to optimize and evaluate microextraction - Stalikas, Constantine; Fiamegos, Yiannis; Sakkas, Vasilios; Albanis, Triantafyllos (Journal of Chromatography A, 2009)
Chemometric experimental design in microextraction plays a crucial role in sustaining the highest quality of analytical data. Making use of the main significant points of chemometric experimental design and microextraction in analytical chemistry we formed the core of this review article. A step-by-step chemometric approach is provided to optimize and validate microextraction-based analytical processes. Significant applications are reported with developments related to microextraction combined with chemometric optimization processes. As it appears from the numerous examples provided in this review, a great number of researchers give credit to the combination of microextraction and chemometrics recognizing that it significantly streamlines sample processing. Moreover, the combination of microextraction with chemometrics addresses problems relating to improvement in detectability and method validation. A worked example on the microextraction of polychlorinated biphenyls is incorporated into the relevant sections of this article and comprehensively provides in a rational and integrated way guidance to people dealing with this subject.